Fences - Washington, Denzel 1954-; Christensen, Charlotte Bruus 1978-; Wilson, August 1945-2005; Davis, Viola 1965- (Universal Pictures Germany GmbH, 2017)
A black garbage collector named Troy Maxson in 1950s Pittsburgh is bitter that baseball's color barrier was only broken after his own heyday in the Negro Leagues, Maxson is prone to taking out his frustrations on his loved ones
Original: USA, 2016
Based on August Wilson's Pulitzer prize-winning novel
Bonusmaterial: Ein grösseres Publikum: von der Bühne auf die Leinwand ; die Umsetzung von Fences: Denzel Washington
Keywords: Theater -- New York (State) -- New York.; African American theater -- New York (State) -- New York.; Race relations -- Drama.; Negro leagues -- Drama.; Man-woman relationships -- Drama.; Fathers and sons -- United States -- Drama.; Fathers and sons -- Drama.; Families -- Drama.; Families, Black -- United States -- Drama.; Ethnische Beziehungen; Theater; Familie; Schwarze; Sohn; Vater; Bürgerrechtsbewegung; New York, NY; Film; DVD-Video